A clinical study of optic nerve involvement in patients with tuberculosis attending a tertiary health care center in North East - Borooah, Mitali; Malakar, Amar Jyoti (International Journal of Research in Medical Sciences, 2021)
Background: To screen for ocular finding of optic nerve involvement in patients with tuberculosis and documents these findings. Methods: The hospital based observational study was carried out in a tertiary care hospital in Assam for the duration of July 2018 to June 2019 in 384 diagnosed cases of tuberculosis patients who fulfil the inclusion criteria during the study period. Results: 11 cases with optic nerve involvement was found out of 384 tuberculosis patients. Most common presenting complain was blurring of vision. Unilateral involvement was maximum. Most common finding was disc oedema. Ocular TB cases was higher in extrapulmonary TB patients. Conclusions: Diagnosis of ocular Tb is mainly presumptive, based on history, clinical examination, adjunctive diagnostic tests and response to anti tuberculous therapy. Amongst 384 TB cases ocular manifestations were found in 11 cases and therefore, we can conclude that ocular manifestations hold significance in extra pulmonary manifestations of TB. So, TB patients need to have routine ocular examination for the early diagnosis and timely management.